Health system readiness for immediate Kangaroo Mother Care (iKMC) among network of care facilities in the Sidama region, Ethiopia: a mixed-method study - Abiy Seifu Estifanos; Hailemariam Negash; Setisemhal Getachew; Dorka Woldesenbet Keraga; Akalewold Alemayehu; Mekdes Shifeta Argaw; Meles Solomon; Fitsum Woldegabriel Belay; Siren Rettedal; Sachiyo Yoshida; Anayda Portela (Gates Open Research, 2026)
Introduction Despite Ethiopia’s remarkable progress in reducing deaths among children under five, neonatal mortality remains high. The provision of immediate Kangaroo Mother Care (iKMC) for clinically unstable preterm and low-birth-weight (LBW) newborns has proven effective in lowering neonatal mortality related to preterm newborns. This study aimed to assess Ethiopia’s health system readiness to integrate iKMC into Level 2 small and sick newborn care (SSNC) units, with a focus on a selected network-of-care facilities in the Sidama region. Methods We employed a mixed-method design. Through a cross-sectional quantitative facility mapping across a network of 25 facilities, data were electronically captured and analyzed in SPSS using descriptive statistics. The qualitative assessment included in-depth interviews and focus group discussions with mothers and family members of preterm or LBW newborns and a range of stakeholders. Data were coded, thematized, and analyzed using the World Health Organization health systems building blocks and the SSNC continuum of care. Results Out of the 25 facilities, 8 (32.0%) had inpatient newborn care units (NCUs) and attended to 16,843 (68.4%) of all mapped births, 1,044 (96.6%) of all preterm births, and 1,143 (94.0%) of all LBW births recorded in the 12-months preceding the assessment. Four facilities with NCUs, admitting 93.4% of preterm and 88.2% of LBW newborns from the catchment area, were identified as eligible to introduce iKMC. All four iKMC-eligible facilities provided antenatal corticosteroids, had trained dedicated health workers to care for preterm or LBW newborns, and offered KMC. Although insufficient, they also had SSNC devices and infrastructure. The qualitative assessment identified facilitators and barriers related to the health system, families’ knowledge, attitudes, engagement, and support, and mothers’ household responsibilities. Conclusion Despite notable health system gaps, hospitals with inpatient NCUs demonstrated modest readiness and willingness to introduce iKMC and create a mother-newborn couplet model of care approach.